2014
DOI: 10.1002/arp.1473
|View full text |Cite
|
Sign up to set email alerts
|

Between Surface and Summit: the Process of Mound Construction at Feltus

Abstract: Geophysical methods that explore depths more than 1 m below the surface were employed at Feltus (22Je500), a Coles Creek period (AD 700-1200) mound-and-plaza group in southwestern Mississippi, USA. It is difficult to assess the internal structure of large platform mounds such as those at Feltus using excavation and traditional geophysical techniques alone. As a result, such investigations often focus only on activities that took place during and after the final stage(s) of construction. Our 2012 research at Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Whereas the main aim of tumuli exploration is the localization of graves, investigations in recent years also focused on the tumulus as a construction itself, either for secure and efficient excavation planning (Polymenakos & Tweeton, ) or for getting insight into the building history of a tumulus (Kassabaum, Henry, Steponaitis, & O'Hear, ). In prospecting burials or tombs, geophysical methods are often used to detect disturbances of the surrounding soil layers or the remains of access tunnels, the so‐called ‘dromoi’.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the main aim of tumuli exploration is the localization of graves, investigations in recent years also focused on the tumulus as a construction itself, either for secure and efficient excavation planning (Polymenakos & Tweeton, ) or for getting insight into the building history of a tumulus (Kassabaum, Henry, Steponaitis, & O'Hear, ). In prospecting burials or tombs, geophysical methods are often used to detect disturbances of the surrounding soil layers or the remains of access tunnels, the so‐called ‘dromoi’.…”
Section: Introductionmentioning
confidence: 99%
“…Archaeologists have often investigated flat‐topped earthen pyramids throughout the American Southeast, commonly called mounds, using a variety of geophysical prospection techniques. Investigators have traditionally used vertical two‐dimensional GPR profiles (Garrison, ; Welch et al ., ; Pluckhahn et al ., ; Thompson et al ., ), and more recently electrical resistivity pseudo‐sections (Monaghan and Peebles, ; Kassabaum et al ., ) and down‐hole magnetic susceptibility (McNutt et al ., ; Rodning et al ., ; Kassasbaum et al ., ) to understand internal mound structure and to interpret the sequence of mound construction episodes. Others have demonstrated the utility of magnetic gradiometry in locating subsurface structural remains on a mound's final summit (Butler et al ., ; King et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Mound studies employing geophysical methods in eastern North America mainly address off-mound features as well as the internal features and structure of extant (although often damaged) mounds rather than leveled mounds (e.g., Betts and Stay 2017;Bigman and Seinfeld 2017;Britt et al 2002;Burks and Locke-Rogers 2015;Dalan 2006;Hammerstedt et al 2017;Hargrave et al 2007;Kassabaum et al 2014;Lynott 1997Lynott , 2015Messerole 2017;Zimmer-Dauphinee 2017) (Mangold and Schurr 2006;Quimby 1941), plowing of its sandy soil led to nearobliteration of most mounds. Magnetic and resistivity survey of several 10-20 cm elevations, followed by test excavations, confirmed that they were mound remnants.…”
Section: Detecting Leveled Moundsmentioning
confidence: 99%
“…Mound studies employing geophysical methods in eastern North America mainly address off-mound features as well as the internal features and structure of extant (although often damaged) mounds rather than leveled mounds (e.g., Betts and Stay 2017; Bigman and Seinfeld 2017; Britt et al 2002; Burks and Locke-Rogers 2015; Dalan 2006; Hammerstedt et al 2017; Hargrave et al 2007; Kassabaum et al 2014; Lynott 1997, 2015; McKinnon and Haley 2017; Messerole 2017; Zimmer-Dauphinee 2017). Studies of Havana Hopewell Middle Woodland mound sites in the Illinois and Mississippi River valleys are no exception, employing geophysical survey primarily at extant rather than leveled earthworks.…”
Section: Detecting Leveled Moundsmentioning
confidence: 99%